Gender differences in adverse childhood experiences, resilience and internet addiction among Tunisian students: Exploring the mediation effect. - Imen Mlouki; Mariem Majdoub; Emna Hariz; Ahlem Silini; Houcem Elomma Mrabet; Nejla Rezg; Sana El Mhamdi (Public Library of Science (PLoS), 2024)
Adverse Childhood Experiences (ACEs) are a common public health issue with a variety of consequences, including behavioral addiction such as Internet Addiction (IA). Despite widespread recognition of this issue, the underlying mechanisms are not well studied in recent literature. Additionally, studies have indicated gender disparities in the prevalence and manifestation of ACEs and IA. The objective of this study was to investigate the mediating effect of resilience on the link between ACEs and IA among high-school students according to gender in Mahdia city (Tunisia). We conducted a cross-sectional survey for two months (January- February 2020), among 2520 schooled youth in Mahdia city (Tunisia). The Arabic-language edition of the World Health Organisation ACE questionnaire was used. The validated Arabic versions of the Adolescent Psychological Resilience Scale and the Internet Addiction Test were the screening tools for resilience and IA. Data were analyzed according to gender. The majority of youth (97.5%) were exposed to at least one ACE with the most prevalent being emotional neglect (83.2%). Exposure to extra-familial ACEs was also high reaching 86.9% with higher rates among boys for all types of social violence. Internet addiction was common among students (50%) with higher prevalence for boys (54.4% vs 47.7%for girls, p = 0.006). Resilience scores were86.43 ± 9.7 for girls vs 85.54 ± 9.79 for boys. The current study showed that resilience mediated the link between ACEs, especially intrafamilial violence, and internet addiction (%mediated = 15.1). According to gender, resilience had a significant mediating role on internet addiction for girls (%mediated = 17) and no significant role for boys. The mediating effect of resilience in the relationship between ACEs and cyberaddiction among schooled adolescents in the region of Mahdia (Tunisia) has been identified.